A Trust Based Neighbor Identification Using MCDM Model in Wireless Sensor Networks - Gautam, Amit K.; Kumar, Rakesh (Recent Advances in Computer Science and Communications, 2021)
Background: Wireless Sensor Network (WSN) is a major technology for the Internet of Things (IoT) and is used within an IoT system to facilitate collaboration of heterogeneous information systems and services. Due to its distributed nature, these networks are highly vulnerable to various security threats which adversely affect their performance. Trust is one of the influential factors that applies in the security of WSNs to have its applications in cloud system, e-commerce etc. The secure and efficient neighbor selection is an issue of Multiple Criteria Decision Making (MCDM), where many Quality of Service (QoS) parameters play a vital role in the process of best neighbor selection. Methods: A dynamic and efficient trust model is proposed in this paper based on the ranking method for recommendation of appropriate secure neighbor node. To rank the available neighbors, we use voting approach and also a hybrid method of Analytical Hierarchy Process (AHP) and Technique for Order Preference by Similarity to the Ideal Solution (TOPSIS) methods. Results: The paper included a case study to demonstrate the effectiveness of proposed method which maximizes the defense against internal attacks. Complexity analysis has been done to show the superiority of the proposed method. Time complexity of the proposed algorithm is O (n2) against the compared algorithm the growth rate of which is O (2n). Conclusion: This method evaluates trustworthiness of neighbor node quantitatively as a fraction in the range 0 and 1. The proposed algorithm when applied, selects the best node among the alternatives.
Keywords: security